2021
DOI: 10.3390/ani11123437
|View full text |Cite
|
Sign up to set email alerts
|

Aristolochic Acid I-Induced Hepatotoxicity in Tianfu Broilers Is Associated with Oxidative-Stress-Mediated Apoptosis and Mitochondrial Damage

Abstract: Aristolochic acid (AA) is a component of traditional Chinese herbs and commonly used for farm animals in China. Over-exposure of AA has been proven to be associated with hepatotoxicity; however, the mechanism of action of AA-I-induced hepatotoxicity remains unknown. In the current study, a subchronic toxicity test was conducted to evaluate the mechanism of AA-induced hepatotoxicity in Tianfu broilers. According to the results, AA-I-induced hepatotoxicity in Tianfu broilers was evidenced by the elevation of liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In 2022, Guo, et al analyzed hepatic metabolomics in their AAI-exposed mice and found that metabolic pathways of glycerophospholipids and arachidonic acid were disturbed [9] . Other studies have suggested oxidative stress and mitochondrial disturbance associated with AA-induced liver injuries using mice [10] , rats [11] , Tianfu chicken [12] , and weaned piglets [13] . However, a comprehensive mode of action (MOA) underlying AA-induced liver injury is yet to be established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Guo, et al analyzed hepatic metabolomics in their AAI-exposed mice and found that metabolic pathways of glycerophospholipids and arachidonic acid were disturbed [9] . Other studies have suggested oxidative stress and mitochondrial disturbance associated with AA-induced liver injuries using mice [10] , rats [11] , Tianfu chicken [12] , and weaned piglets [13] . However, a comprehensive mode of action (MOA) underlying AA-induced liver injury is yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…The genotoxicity of AA-induced liver injury has been extensively evaluated in vitro and in vivo, suggesting an AT◊TA " ngerprint" mutation that was associated with AA-induced hepatocellular carcinoma [5][6][7] . The nongenotoxic MOA for CILI generally involves receptor-mediated processes or non-receptor-mediated processes, the latter including cytotoxicity, oxidative stress, hormonal perturbation, immunosuppression, et al For AA-induced liver injury in particular, the involvement of cytotoxicity [15,16] and oxidative stress [10][11][12][13] have been reported in multiple studies, whereas the molecular initiating event or the early molecular events are yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%